2005
DOI: 10.1038/sj.cgt.7700908
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte chemoattractant protein-1 gene delivery enhances antitumor effects of herpes simplex virus thymidine kinase/ganciclovir system in a model of colon cancer

Abstract: Suicide gene therapy using the herpes simplex virus thymidine kinase/ganciclovir (HSV-tk/GCV) system is a well-characterized tool for cancer gene therapy; however, it does not yet exhibit sufficient efficacy to cure patients of malignancies. We have reported that adenovirally delivered monocyte chemoattractant protein (MCP)-1 augmented the antitumor effects of the HSV-tk/GCV system in an athymic nude mouse model. The current study, which uses an immunocompetent mouse model of colon cancer, was designed to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…In one hand, CCL2 can potentiate both the innate and acquired immune responses that inhibit tumor growth through recruiting immune cells to enter the tumors and enhance contact-dependent cytolysis of tumor cells (33)(34)(35). On other hand, CCL2 induces macrophage accumulation and cyclooxygenase-2 expression promoting inflammation in colorectal adenoma epithelium, which has been reported to promote tumor progression in autocrine and paracrine fashions (36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…In one hand, CCL2 can potentiate both the innate and acquired immune responses that inhibit tumor growth through recruiting immune cells to enter the tumors and enhance contact-dependent cytolysis of tumor cells (33)(34)(35). On other hand, CCL2 induces macrophage accumulation and cyclooxygenase-2 expression promoting inflammation in colorectal adenoma epithelium, which has been reported to promote tumor progression in autocrine and paracrine fashions (36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…6 We further demonstrated that the antitumor effects depended on the activation of macrophages. 4,5 The adenovirus-specific spatial and temporal expression pattern may result in the production of the transgene for a limited time.…”
Section: Introductionmentioning
confidence: 73%
“…5fluorocytosinewas administered into the peritoneal cavity. All mice in the control groups had tumour progression, but tumour growth was significantly inhibited in the treated mice 73 . Chemo-gene and radiation-gene therapies are the combinations of gene therapy with chemotherapy or radiation therapy respectively.…”
Section: Issn: 0975-8232mentioning
confidence: 99%